Stability of solutions constructed by the wave front tracking method for conservation laws. (February 2023) - Ebata, Takanori; Ohwa, Hiroki
Abstract: We prove the L loc 1 stability of sequence of piecewise constant solutions constructed by the wave front tracking method for conservation laws. As a result, we can see concretely the convergence rate of sequence of piecewise constant solutions constructed by the wave front tracking method for conservation laws.